Conserved dual-mode gene regulation programs in higher eukaryotes. Issue 5 (23rd February 2021) - Lee, Jun-Yeong; Song, Jawon; LeBlanc, Lucy; Davis, Ian; Kim, Jonghwan; Beck, Samuel
Abstract: Recent genomic data analyses have revealed important underlying logics in eukaryotic gene regulation, such as CpG islands (CGIs)-dependent dual-mode gene regulation. In mammals, genes lacking CGIs at their promoters are generally regulated by interconversion between euchromatin and heterochromatin, while genes associated with CGIs constitutively remain as euchromatin. Whether a similar mode of gene regulation exists in non-mammalian species has been unknown. Here, through comparative epigenomic analyses, we demonstrate that the dual-mode gene regulation program is common in various eukaryotes, even in the species lacking CGIs. In cases of vertebrates or plants, we find that genes associated with high methylation level promoters are inactivated by forming heterochromatin and expressed in a context-dependent manner. In contrast, the genes with low methylation level promoters are broadly expressed and remain as euchromatin even when repressed by Polycomb proteins. Furthermore, we show that invertebrate animals lacking DNA methylation, such as fruit flies and nematodes, also have divergence in gene types: some genes are regulated by Polycomb proteins, while others are regulated by heterochromatin formation. Altogether, our study establishes gene type divergence and the resulting dual-mode gene regulation as fundamental features shared in a broad range of higher eukaryotic species.